Development of DNA macroarrays for rapid detection of drug resistance in Hepatitis B virus - La, Thi Quynh Nhu; Pham, Tien Dung; Le, Quang Hoa (Old Journal, 2019)
DNA macroarrays containing 7 wild-type probes and 12 mutant-type probes were successfully developed to detect common mutations associated with the resistance of Hepatitis B virus (HBV) to Lamivudine (LAM), Adefovir (ADV) and Entecavir (ETV). These mutations include rtL180M and rtM204V/I, associated with LAM resistance; rtA181T/V and rtN236T, associated with ADV resistance; rtL180M, rtM204V/I, rtT184S/G, rtS202I and rtM250V/I, associated with ETV resistance. The optimal conditions for DNA macroarray hybridization in 2-ml eppendorf tubes were: hybridization temperature of 54℃, rotation speed of 600 rpm, amount of PCR product of 20 µl. Under these optimal conditions, all target mutations were accurately detected by DNA macroarrays without false positive problems due to cross-hybridization. The main advantages of this new method, based on DNA macroarrays for detection of drug resistance in HBV, are rapidity and simplicity (no special equipment required).